Endothelial progenitor cells, atheroma burden and clinical outcome in patients with coronary artery disease. Issue 11 (6th February 2013) - Padfield, Gareth J; Tura-Ceide, Olga; Freyer, Elizabeth; Barclay, George Robin; Turner, Marc; Newby, David E; Mills, Nicholas L
Abstract : Objective: We wished to determine the effect of an acute coronary syndrome (ACS) on putative endothelial progenitor cell (EPC) populations, and define their relationship to coronary artery disease (CAD) severity and clinical outcome, in order to clarify their clinical relevance. Design and setting: A prospective cohort study conducted in a tertiary referral cardiac centre. Patients: Two-hundred-and-one patients undergoing coronary angiography for suspected angina or ACS. Main outcome measures: Putative EPC populations were determined by flow cytometry. CAD was quantified using the Gensini scoring system. Survival free from revascularisation, recurrent myocardial infarction and death were determined at 3 years. Results: Circulating CD34 + VEGFR-2 + and CD34 + VEGFR-2 + CD133 + cells were rare (<0.007% of mononuclear cells), were not increased in patients with ACS, and were unrelated CAD severity or clinical outcome (p>0.1 for all). By contrast, CD34 + CD45 − cells were increased in patients with CAD compared with those with normal coronary arteries (p=0.008) and correlated with atheroma burden (r=0.44, p<0.001). Increased concentrations of circulating CD34 + CD45 − cells were associated with a shorter cumulative event-free survival (p<0.02). Proangiogenic monocytes (CD14 + VEGFR-2 + Tie-2 + ) and endothelial cell-colony forming units were increased in patients with ACS (p<0.01 for both), however, concentrations reflected myocardial necrosis, and did not predict the extent of CAD or clinical outcome. Conclusions: Traditional EPC populations, CD34 + VEGFR-2 + and CD34 + VEGFR-2 + CD133 + are not related to the extent of CAD or clinical outcome. However, CD34 + CD45 − cells are increased in patients with CAD and predict future cardiovascular events. It is likely that CD34 + CD45 − concentrations reflect the extent of vascular injury and atheroma burden.